The impact of technology frustration and consumer passion on consumer evaluation shift in case of mobile apps - Bidyut Hazarika; Utkarsh Shrivastava; Timothy McBush Hiele; Chi Pham (Acta Psychologica)
Online consumer ratings play a crucial role in determining a product's long-term success. This study examines the direct impact of consumer technology frustration and consumer passion on app ratings and evaluations over time. Beyond these direct effects, we propose that consumer passion moderates the relationship between technology frustration and evaluations—specifically, passion amplifies the negative impact of frustration, making a double-edged sword. Using data from the Google Play Store, we tracked the top 20,000 Android apps over three months (September 29, 2023–January 1, 2024), constructing a panel dataset with 11,568 panels and 13,810 observations. Our disaggregated analysis—considering download volume, app age, price, and publisher rating—confirms the hypothesized effects. Remarkably, established apps and publishers are particularly vulnerable to the intensified negative substitution effect. Our findings suggest that new app developers should prioritize a functional, intuitive platform and enhance it over time to foster consumer passion. Meanwhile, established apps must actively minimize technological frustration, as passionate users' negative experiences can significantly impact ratings and future downloads.